STUDI PEMBANGUNAN RUANG TERBUKA HIJAU PUBLIK DI KECAMATAN PONTIANAK KOTA PADA KOTA PONTIANAK - Haidar, Muhammad; Thamrin, Eddy; Latifah, Siti (JURNAL HUTAN LESTARI, 2019)
Green Open Space (RTH) is an area that extends / lanes and or groups, which use more open, where plants grow, both those that grow plants naturally and deliberately planted. In Law No. 26 of 2007, specifically mandates the need for the provision and utilization of green open spaces, the proportion of which is set at least 30% percent of the total area of the city, namely (20% of public green space and 10% private RTH). The study aims to determine the suitability of the implementation of green open space development in Pontianak city sub-district with Pontianak City RTRW and find out the causes that are not achieved if the green open space has not run smoothly. The research method used a survey method and ground check of green open space distribution in Pontianak city sub-district. The interview technique was to find out the perceptions of the surrounding community towards RTH areas in Pontianak Kota Sub-district. The results of the study from the Interpretation of IKONOS 2017 Images and the 2018 ground check in Pontianak Kota District in the year there were 22 green open spaces. The area of calculation of Existing and RTRW 2013-2033 almost reached the target, RTH Park reached 98.63%, RTH Funeral 89.83%, RTH Field 94.96%, and RTH Green Line had reached 104% of the RTRW 2013-2033Keywords: Development, Green Open Space, Pontianak, RTH Public